(untitled) (Ozone Therapy Global Journal, 2011)
The ozonetherapy is being known and applied more and more in different countries of the world. The fact is that there is more interest from health professionals to know how medical ozone works and what it benefits are. The numbers confirm this fact. On one hand the number of ozonetherapists keeps growing all around the world. Recent statistics compiles by the AEPROMO Legal Advisor Roberto Quintero and annexed at the last Professor Velio Bocci’s paper published in this current issue of our journal, indicate that in Germany, the country where the ozone was discovered 11000 health professionals practice this therapy. The second country in number of ozonetherapists is China with 5000, followed by Russia with 3500, then Italy with 3000. Around the world there are more than 26100 health professionals who practice the medical therapy of the ozone. These figures are only an estimate. With all likehood its number is higher. On the other hand health professionals are more conscious than ever, that the practice on ozone-therapy must require previous theoretical and practical knowledge. However many problems are plaguing this therapeutic modality, resistance it still found within the medical community and its recognition in the legal field requires more and coordinated efforts. Only four countries, have taken serious efforts for its official recognition, those are: Cuba, Russia, Spain and partially Italy.